An exploratory qualitative study to identify factors affecting requirements elicitation and fact finding while developing health care knowledge management systems in Pakistan - Arshad, Arfan; Noordin, Mohamad Fauzan; Othman, Roslina (Publications International, 2017)
Requirements elicitation or Requirements gathering is the most important part of any project irrespective of the system development methodology being used. A number of fact- finding techniques have been introduced in this respect. Many Healthcare Knowledge Management System (HKMS) projects start with an incomplete or incorrect list of requirements which ultimately result in halting, delaying or failure of those projects. Requirements elicitation is the most important step of the requirements discovery process which focuses on fact-finding and data acquisition by using different techniques. The purpose of this study is to identify and determine those factors which affect the requirements gathering and discovery process and cause hindrance individually or collectively during fact-finding process. This ultimately results in misguiding the direction of the project. Dealing with such factors will help in developing proper and appropriate system requirements specifications. Furthermore, this study will also pave the way to find out solutions to cater and mitigate the occurrence and existence of such factors.